The Relationship between Student Discipline Attitudes and a Child Friendly School Environment - Nahuda; Soleh , Muhamad (CV ODIS, 2023)
This study aims to obtain precise, correct, valid reliable and reliable data about the Influence of a Child-Friendly School Environment on Student Discipline at SMAN 107 East Jakarta, How much influence between the two is sufficient or moderate and the factors that influence it. This study used the